Women Stereotypes on Margaret Atwood’s Novel “The Handmaid’s Tale” - Yuniar Fatmasari; Lela Ainu Sakina (Metaphor, 2023)
The patriarchal culture tradition has existed for a long time. This social system encourages various types of stereotypes, especially for women. Men's dominance over women makes women's existence stereotyped with the issue of social class and gender segregation which causes dystopian life. This study is to show how novels can be used as social critiques of woman discrimination. The Handmaid’s Tale by Margaret Atwood is one of the literary works that addresses the topic of gender stereotyping across how the stories happened. This research uses it to get the data on stereotype aspect especially for the woman stereotype that appears in the novel. The objective of this study is to find out the types of woman stereotypes realized in Margaret Atwood’s Novel “The Handmaid’s Tale”. Therefore, the method used is descriptive qualitative. The study’s results show that the women in the novel especially the lower status women are stereotyped as sexual partner, reproducer, erotic object, motherhood and housewife, weak creatures, lacked in political and education, and having emotional expressiveness. This study's impact is encouraging women to engage in critical thinking and not make themselves objects to men.